SWOT Analysis of Albania for Foreign Direct Investment - Zisi, Alma (Mediterranean Journal of Social Sciences, 2012)
Foreign direct investment plays an important role in economic development of the country. For this reasons, governments useincentive policies to attract more foreign investors. Albania has attracted a remarkable amount of FDI inflows in recent years. In keysectors like mining, banking and telecoms, the Albanian economy is dominated by foreign investors. That suggests that there is morepossibility for increased FDI in the country. It is important that the types of FDI Albania attracts are those with the potential to benefit theeconomy. The high share of FDI in certain industries of the country is partly a sign of weaknesses in the domestically-owned part ofthese industries. The objective of this study is to perform a SWOT analysis of Albania for FDI after covering the determinants and hosteconomy effects of FDI.